The revolving door of HIV care: Revising the service delivery cascade to achieve the UNAIDS 95-95-95 goals. - Peter Ehrenkranz; Sydney Rosen; Andrew Boulle; Jeffrey W Eaton; Nathan Ford; Matthew P Fox; Anna Grimsrud; Brian D Rice; Izukanji Sikazwe; Charles B Holmes (PLoS Medicine, 2021)
Peter Ehrenkranz and co-authors present a cyclical cascade of care for people with HIV infection, aiming to facilitate assessment of outcomes.